2013
DOI: 10.1002/jaba.80
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the stranger safety abduction-prevention program and parent-conducted in situ training

Abstract: Using a control group design, we evaluated the effectiveness of the Stranger Safety DVD (The Safe Side, 2004) and parent training of abduction-prevention skills with 6- to 8-year-old children. Children in the training or control group who did not demonstrate the safety skills received in situ training from their parents. There was no significant difference in safety skills between the training and control groups after the training group viewed the DVD. Children in both groups scored significantly better after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Children were more mixed in their motor response to the lure from the unknown confederate. Consistent with past research (Miltenberger et al, 2013), withdrawal from the Interpersonal Safety Skills 19 unfamiliar confederate was the least common response comprising slightly less than 30% of the current sample. Furthermore, 33% of the children who participated actively approached the confederate upon receiving the abduction lure.…”
Section: Interpersonal Safety Skills 18supporting
confidence: 81%
“…Children were more mixed in their motor response to the lure from the unknown confederate. Consistent with past research (Miltenberger et al, 2013), withdrawal from the Interpersonal Safety Skills 19 unfamiliar confederate was the least common response comprising slightly less than 30% of the current sample. Furthermore, 33% of the children who participated actively approached the confederate upon receiving the abduction lure.…”
Section: Interpersonal Safety Skills 18supporting
confidence: 81%
“…For example, although previous research has not examined the effect of IST on disclosure intentions and confidence specifically, consistent with the current study, Johnson et al (2006) found that when IST was added to a program using a BST approach, there was greater maintenance of desired interpersonal safety skills (i.e., lure refusal, withdrawal and disclosure) at a 3-month follow-up relative to BST alone. Results are also consistent with those observed in Beck and Miltenberger (2009) where use of interpersonal safety skills (i.e., withdrawal and disclosure) was most effective in a video-based education program þ IST condition, and Miltenberger et al (2013) where the addition of parentadministered IST resulted in significant improvement in interpersonal safety skill use (i.e., withdrawal and disclosure) for children, compared to that demonstrated in participation in the program alone and waitlist groups.…”
Section: Ist As Booster To a Protective Education Programsupporting
confidence: 83%
“…This was done so as to prevent potential desensitization of participating children to future risk situations, where after multiple “test” risk scenarios they might believe any future risk encounters are another simulated test. However, as addressed by Miltenberger et al (2013), the best method to measure safety skills is by direct behavioral measures of skill. Future research may seek to address this methodological limitation by utilizing a wider range of in situ assessments to assess the impact of the IST on direct disclosure and thus avoid potential desensitization to any single risk context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a 2018 survey by The Family Online Safety Institute [33], parents indicated that "stranger danger" scenarios are their top online safety concern. For many years, the phrase "stranger danger" has been used to teach children about issues in physical safety by telling them to stay away from people they do not know as these strangers may mean them harm [16]. Recently, news media have reported numerous stranger danger and cyberbullying incidents involving young children using social media apps.…”
Section: Introductionmentioning
confidence: 99%